2014
DOI: 10.5114/wo.2014.42724
|View full text |Cite
|
Sign up to set email alerts
|

Review Actual status of therapeutic vaccination in non-small cell lung cancer

Abstract: Lung cancer is the leading cause of cancer-related death worldwide. Although treatment methods such as surgery, radiotherapy and/or chemotherapy have improved, prognosis remains unsatisfactory, and developing new therapeutic strategies is still an urgent matter. Immunotherapy is a novel therapeutic approach wherein activated immune cells can specifically kill tumour cells. Several lung cancer vaccines have demonstrated prolonged survival time in phase II and III trials, and several clinical trials are under in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…Cancer cytotherapy is a novel therapeutic approach with great potential [ 22 24 ]. Since the report of the first DCs-based cancer vaccine clinical trial in 1995 [ 25 ], a lot of trials have been designed and conducted [ 26 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Cancer cytotherapy is a novel therapeutic approach with great potential [ 22 24 ]. Since the report of the first DCs-based cancer vaccine clinical trial in 1995 [ 25 ], a lot of trials have been designed and conducted [ 26 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…These studies have shown that a subset of patients benefit from vaccination, with clinical benefit being confined to those who respond most robustly in immunologic terms. The overarching lesson from these trials is that responses to therapeutic vaccines can be significant, but are generally limited to a subset of patients . We hypothesized that using a vaccine as a preventive strategy could enable the polarization of an immune response capable of successfully eliminating early lesions and preventing tumor development in the lung.…”
Section: Introductionmentioning
confidence: 99%
“…Lung cancer is becoming the leading cause of cancer-associated mortality worldwide, particularly in China ( 1 , 2 ). For patients with lung cancer, resistance to therapy is a common phenomenon, which threatens the success of the treatment currently used against the disease.…”
Section: Introductionmentioning
confidence: 99%